The chupacabras of the Río Grande - Gidwitz, Adam; Bowles, David (David O.) (Gidwitz, Adam. Unicorn Rescue Society, 2019)
"Uchenna and Elliot travel with Professor Fauna to the Texas-Mexico border to save the region's animals and help bring a divided community back together with the help of locals"--